TOURISM INDUSTRY; REKAM JEJAK PERISTIWA DAN PERUBAHAN BUDAYA - Abdurrahman, Abdurrahman (JURNAL KARSA (Terakreditasi No. 80/DIKTI/Kep/2012), 2012)
Abdurrahman (Pemerhati Sosial dan Budaya, nomor kontak 087750524017, victorio@yahoo.com, bermukim di Artodung-Galis-Pamekasan)     Abstract Tourism that has been actually existed since the new civilization for human being. The end of world war II is considered the starting point of modern tourism. It is blowing up in the big scale as one of the social and economic power. As phenomena, that is natured by multy aspects, touris, not only serves the smell of prosperity but also  arisesthe culture shift in social frame especially for the local community. Its positive and negative implication becomes an integral part such as two sides coin. In this context, there is one thing to consider  that human factor and local culture entity cannot be denied. It means the local community life must not be separated from its root to empasize the commercial aspect of tourism. As matter of fact,  the true orientation of tourism points to tourism industry that still concerns the humanity and rotates the culture of nature. Kata-kata kunci tourism, jejak sejarah, interaksi sosial, pergeseran sosial budaya